Variation of Physico-Chemical Attributes of Seed Oil Between Two Developing Cultivars of Sesame Grown Under Similar Agroclimatic Conditions in Pakistan - Ahmad, Naveed; Anwar, Farooq; Mahmood, Zahed; Ali Shahid, Shaukat; Shakir, Imran; Latif, Shabnem (Asian Journal of Chemistry, 2014)
The present work appraises variation of physico-chemical attributes of seed oils between two cultivars (V-96006 & V-90005) of sesame (Sesamum indicum L.) grown under similar agroclimatic conditions. Sesame seeds of cultivar V-96006 & V-90005 had oil, 41.20 and 46.95 %; moisture, 8.09 and 9.54 %; protein, 32.05 and 30.19 %; fiber, 2.41 and 2.10 % while ash 4.39 and 4.78 %, respectively. The extracted sesame seed oils had iodine value between 107 and 110 (g of I/100 g of oil), refractive index (40 °C) 1.4624 and 1.4638, density (24 °C) 0.87 and 0.88 mg/mL, free fatty acids 0.49 and 0.54 %, saponification value 190.24 and 190.95 mg of KOH/g of oil and unsaponifiable matter 2 and 2.60 %, respectively. The tested oils, in terms of measurements of peroxide value (1.96-2.20 meq/kg), conjugated dienes (2.01-2.38) and conjugated trienes (0.64-0.66) exhibited good oxidative state. The amounts of total tocopherols (<span style="font-size: 12pt; font-family: Symbol; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">a, <span style="font-size: 12pt; font-family: Symbol; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">g and <span style="font-size: 12pt; font-family: Symbol; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">d) in the tested sesame oils of V-96006 & V-90005 cultivars were found to be 619.5 and 644.6 mg/kg, respectively with <span style="font-size: 12pt; font-family: Symbol; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">g-tocopherol as the principal compound. GLC analysis of the oils revealed the occurrence of mainly linoleic acid (C18:2) 44.52, 44.27 %; oleic acid (C18:1) 39.34, 40.07 %; palmitic acid (C16:0) 9.82, 9.23 % and stearic acid (C18:0) 5.21, 4.98 %, respectively. Small amount of linolenic acid (C18:3) < 1.0 % was also detected. The results of the present study showed that both of these sesame cultivars, except tocopherols, have comparable physico-chemical attributes and thus advocate selection of this potential oil seed crop for cultivation under the local agroclimatic conditions to produce good quality high-linoleic oil.